NOISE TERMS PADA SOLUSI DERET DEKOMPOSISI ADOMIAN DALAM MENYELESAIKAN PERSAMAAN DIFERENSIAL PARSIAL - Heni Kusnani; Leli Deswita; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses the solution of nonhomogeneous linear partial differential equa-tions of first order and homogeneous nonlinear partial differential equations of second order using Adomian decomposition method. The obtained solution is of the form series. In the series solution of nonhomogeneous linear partial differential equations of the first order appears noise terms phenomenon, which is the same terms but with opposite sign, so that the solution obtained is a finite series.